Pengungkapan Diri (Self-Disclosure) Mahasiswa - Daharnis dkk. Daharnis dkk (Universitas Negeri Malang, 2016)
This study was aimed at describing self-disclosure of the students of State University of Padang (UNP). The sample consisted of 258 (32 males and 225 females) chosen by using cluster random sampling technique. The data were collected by questionnaire and analyzed by percentage and t-test. The findings reveal that self-disclosure of students of UNP is still low. There is no significant difference in self-disclosure between male and female students. The students tend to be more open to their father and mother than to other target persons. The students are more open in their attitudes and opinion, taste and interest, and education and job than in their finance, personality, and body aspects